Temperature, Pressure, and Composition of the Mantle Source Region of Late Cenozoic Basalts in Hainan Island, SE Asia: a Consequence of a Young Thermal Mantle Plume close to Subduction Zones? - Wang, Xuan-Ce; Li, Zheng-Xiang; Li, X.; Li, J.; Liu, Y.; Long, W.; Zhou, J.; Wang, F. (Oxford University Press, 2012)
Basaltic lavas from Hainan Island near the northern edge of the South China Sea have an age range of between late Miocene (about 13 Ma) and Holocene, with a peak age of late Pliocene to middle Pleistocene. The basaltic province is dominated by tholeiites with subordinate alkali basalts. Most analysed samples display light rare earth element (LREE) enriched REE patterns and ocean island basalt (OIB)-like incompatible element distributions. The basalts contain abundant undeformed high-Mg olivine phenocrysts (up to Fo90•7) that are high in CaO and MnO, indicating high-magnesian parental magmas. Independent barometers indicate that clinopyroxenes in the basalts crystallized over a wide range of pressures of 2–25 kbar (dominantly at 10–15 kbar) and that the melt cooled from about 1350°C to 1100°C during their crystallization. The compositional characteristics of the basalts indicate that their generation most probably involved both low-silica and high-silica melts, as represented by the alkali basalts and tholeiites, respectively. Our results show that the source region for the Hainan basalts is highly heterogeneous. The source for the tholeiites is mainly composed of peridotite and recycled oceanic crust, whereas the source for the bulk of the low-Th alkali basalts consists predominantly of peridotite and low-silica eclogite (garnet pyroxenite). Some high-Th (≥  4 ppm) alkali basalts may have been produced by partial melting of low-silica garnet pyroxenite (eclogite). We estimated the primary melt compositions for the Hainan basalts using the most forsteritic olivine (Fo90•7) composition and the most primitive bulk-rock samples (MgO > 9•0 wt % and CaO >8•0 wt %), assuming a constant Fe–Mg exchange partition coefficient of KD = 0•31 and Fe3+/FeT = 0•1.The effective melting pressure (Pf) and melting temperature (T) of the primary melts are Pf = 18–32 kbar (weighted average = 23•8 ± 1•8 kbar) and T = 1420–1520°C for the tholeiites, and Pf = 25–32 (weighted average = 28•3 ± 1•4 kbar) and T = 1480–1530°C for the alkali basalts. The Pf  –T data form an array that plots systematically above the dry lherzolite solidus but below the base of the lithosphere (~55 km) and intersects the dry peridotite solidus at a pressure of about 50 kbar. The mantle potential temperature beneath Hainan Island, based on the estimate primary melt compositions, varies from about 1500 to 1580°C with a weighted average of 1541 ± 10°C. The high-magnesian olivine phenocrysts, high mantle potential temperature, and the presence of recycled oceanic crust in the source region provide independent support for the Hainan plume model that has previously been proposed largely based on geophysical observations. The Hainan plume thus provides a rare example of a young mantle plume associated with deep slab subduction.